Aplikasi Pemesanan Barang pada CV. Wanda berbasis SMS - Fatmasari (LPPM STMIK ANTAR BANGSA, 2024)
Ordering goods is something that is usually done during a transaction, whether it is done conventionally or using technology. CV Wanda is a business that operates as a soft drink distributor that provides distribution services to agents, which in this case started to experience problems due to the lack of service provided for orders of goods requested by the agent. This is because CV Wanda still uses conventional methods in carrying out this process. Therefore; In order to make it easier for agents to place orders, a technological touch is needed that can help both parties. One way is to use SMS as an integrated means of ordering goods. This was chosen because SMS signals can still reach more remote areas in the process of sending order data which is expected to help minimize existing problems.